Faktor-faktor yang Mempengaruhi Efektivitas Pengelolaan Kelas B Taman Kanak-kanak di Kota Ternate - Rinelsa R Husaen (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2021)
This study uses a quantitative approach to the ex post facto method with aims to determine the effect of:1) educators’ work motivation on classroom management; 2) educators’ teaching experience onclassroom management; 3) classroom facilities on classroom management. The study sample size of 76people. The instrument used in this study was a questionnaire. The data were presented by usingdescriptive statistics and regression analysis. Meanwhile, regression analysis shows that 1) there is nosignificant effect of educators’ work motivation on classroom management (P(α)= 0.275>0.05), 2) thereis no significant effect of educators’ teaching experience on classroom management (P(α)= 0.225>0.05), 3)there is no significant effect of classroom facilities on classroom management (P(α)= 0.201>0.05), and 4)there is no significant effect of educators’ work motivation, educators’ teaching experience, and classroomfacilities on the kindergarten classroom management (Rxy = 0.062) (P(α)= 0.103>0.05).Keywords: Classroom Management, Educators’ Work Motivation, Educators Teaching Experience,